Frailty predicts mortality and complications in chronologically young patients with traumatic orthopaedic injuries. Issue 12 (December 2018) - Rege, Rahul M.; Runner, Robert P.; Staley, Christopher A.; Vu, CatPhuong Cathy L.; Arora, Sona S.; Schenker, Mara L.
Abstract: Background: As morbidity and mortality from traumatic orthopaedic injuries continues to rise, increased research is being conducted on how to best predict complications in at risk patients. Recently, frailty indices have been validated in a variety of surgical subspecialties as predictors of morbidity and mortality. However, the vast majority of research has been conducted on geriatric patient populations, with little evidence on patients who are chronologically young. The purpose of this study was to evaluate the role of a modified frailty index (mFI) in predicting mortality and complications after pelvis, acetabulum, and lower extremity trauma in patients of all ages. Methods: The American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database was queried from 2005 to 2014 for all patients who underwent surgery for pelvis, acetabulum, and lower extremity trauma. The sample size was divided into geriatric (age ≥ 60) and young (age < 60) cohorts. The mFI score was calculated for each patient. Bivariate analysis was performed using logistic regression and a chi-square test to determine the relationship between mFI and both primary and secondary outcomes while adjusting for age. Univariate analysis and multivariate analyses were performed. All analyses were done using SAS 9.4 (Cary, NC) and a p < 0.05 was considered significant. Results: 56, 241 patients were identified to have undergone surgery for pelvis, acetabulum, or lower extremity trauma. 28% of patients were identified under the age of 60. In the young cohort, mFI was a strong predictor of thirty-day mortality (OR 11.02, 95% CI 6.26–19.39, p < 0.001). With regards to Clavien-Dindo grade IV complications, MFI is also a strong predictor in the young cohort (OR 28.82, 95% CI 16.05–51.77, p < 0.001). Conclusion and relevance: The mFI score was a significant predictor of morbidity and mortality in chronologically young orthopaedic trauma patients. The use of the mFI score can provide an individualized risk assessment to interdisciplinary teams for perioperative counseling and to improve outcomes.